An Activity to Promote Recognition of Unintentional Plagiarism in Scientific Writing in Undergraduate Biology Courses - Zwick, Melissa (J Microbiol Biol Educ, 2019)
Unintentional plagiarism frequently occurs in undergraduate writing assignments because students are unaware of the complexity of correct paraphrasing and citation rules. There is often a lack of formal instruction in science courses on proper paraphrasing and citation to reduce plagiarism. To address this deficit, we developed a brief activity to teach students to recognize the range of paraphrasing and citation errors that can result in plagiarism. The activity was used in a biology-focused scientific literacy course, but it can be incorporated into different instructional settings, with undergraduate students of all levels. During this classroom activity, part 1 addresses the nuances associated with proper paraphrasing and citation in scientific writing and part 2 asks students to practice paraphrasing and properly citing a passage from a scientific source. Pretest results revealed that students were proficient at identifying plagiarism when a citation error occurred but were less proficient at recognizing improper paraphrasing (patchwriting or direct plagiarism). Posttest results indicated that the activity was effective at increasing the students’ ability to recognize a paraphrasing error even when a correct citation was present. Students also reported higher confidence in their understanding of what constitutes plagiarism and that they are more confident in their ability to properly paraphrase and cite scientific source content.